Prevalence and Distribution of High-Risk Genotypes of HPV in Women with Severe Cervical Lesions in Madrid, Spain: Importance of Detecting Genotype 16 and Other High-Risk Genotypes. (19th September 2010) - Mateos Lindemann, Maria Luisa; Sánchez Calvo, Juan Manuel; Chacón de Antonio, Jesús; Sanz, Itziar; Diaz, Esperanza; Rubio, Maria Dolores; de la Morena, Maria Luisa
Abstract : Background . Persistent infection with high-risk human papillomavirus (HR-HPV) has been demonstrated to be the necessary causal factor for developing cervical cancer. To know the most prevalent HR-HPV in different geographical areas is important to design diagnostic tests and implementation of vaccines. Objectives . The goal of this study is to evaluate the prevalence of HR-HPV in a total of 1001 patients, 198 with normal cytology results, 498 with low-grade squamous intraepithelial lesion (LSIL), and 205 with high-grade squamous intraepithelial lesion (HSIL) who attended our gynaecology department for opportunistic screening of HPV infection. Study design . Cervical samples were taken in a PreservCyt vial (Cytyc Corporation, Boxborough, MA). Hybrid capture assay was carried out following the manufacturer's instructions (Digene Corp., Gaithersburg, MD). All samples were further studied with polymerase chain reaction (PCR) (Linear Array HPV Genotyping Test, Roche Diagnostics, Mannheim, Germany). Results . Genotype 16 was the most prevalent HR-HPV in the three groups, 17.8% in the patients with normal cytology results, 22.3% in the LSIL group, and 60% in the HSIL group. Genotype 18 had a very low prevalence in all groups. Other HR-HPV genotypes such as genotype 31, genotype 58 and genotype 52 were found in significant numbers in HSIL patients. Discussion . Our data show that genotypes 16, 31, 58, and 52 are the most prevalent HR-HPV in cervical samples with severe intraepithelial lesion in Spain. There may be some geographical variation in prevalence of carcinogenic types, and it must be considered for designing diagnostic tests and vaccine.